P2-S2.06 Becoming a sex worker: the nexus between violence, gender disadvantage and poverty. (10th July 2011) - Shahmanesh, M; Wayal, S; Cowan, F
Abstract : Background: Community mobilisation of female sex workers is integral to India's HIV prevention strategy. Sex workers often become infected by HIV soon after initiation into sex work. The societal factors that propel women into sex work may also inhibit the self-efficacy/agency required to access healthcare and adopt safer sexual behaviour. Methods: In-depth interviews were conducted with sixteen purposively selected (based on HIV status, ethnicity, age, area, and type of sex work) female sex workers in Goa, India (December 2004–December 2005). We interrogated the life narratives to explore the nexus between the social context/risk environment and self-efficacy/agency. Results: The narratives showed a dynamic interplay between underlying vulnerabilities, precipitating factors, and the route through which women gain entry into the sex trade: The ubiquitous mitigating theme that emerged was violence in childhood and youth. This ranged from dysfunctional and violent family life, sexual violence, and violence from intimate male partners. The other underlying vulnerabilities that emerged from the narratives were also manifestations of gender disadvantage, namely being unwanted; sexual naïveté and young marriage/sexual initiation; repression of sexuality, desire and entrapment in loveless marriages; and lack of life skills and low self-esteem. The loss of social support through bereavement, abandonment or financial need, were the commonest events that precipitated entry into sex work. Becoming a sex worker was frequently an expression of agency in a context with few other economically viable choices for women. The clearest division in the route into sex work was between traditional caste-based sex workers (devadasi) and those who were either introduced by peers, or sold through a broker; however the underlying and precipitating factors for both routes were remarkably similar. Mostly, initiation was described as a complex process that was mediated through peers. Conclusion: The interplay between caste, economy, gender, and violence drives the initiation into sex work, which is one of the few viable choices for the women. HIV prevention interventions therefore need to work upstream to impact upon the context within which women enter sex work and downstream to strengthen their agency. The peers who introduce women into sex work are potentially important vehicles to deliver "HIV prevention services and reduce the adverse health outcomes of sex work."